Exploring the embodied basis of being through Merleau-Ponty and dance: a conversation between philosophy and practice - Purser, Aimie Christianne Elizabeth. (2008)
Merleau-Ponty suggests that a non-dualistic understanding of embodied being must start from a theory of embodied practice. This allows us to think in terms of a body-subject, rather than seeing the body as object, and thus to consider embodiment as the basis of subjectivity and intersubjectivity. Further to this, I contend that if we are to truly move away from dualism in our understanding of human being, we need not only to conceptualise embodiment adequately in philosophical terms, but also to engage with lived embodied practice.